Political and Institutional Commitment to a Common Currency - Mussa, Michael (American Economic Review, 1997)
A stroll along the first floor corridor at the International Monetary Fund's Washington headquarters reveals the fundamental and indisputable fact that political considerations, rather than purely economic concerns, are the predominant practical determinants of the domain of operation of currency regimes. Despite the theory of optimum currency areas which might suggest alternative outcomes, with few exceptions, the empirical regularity is one country, one money. Even the exceptions help prove the rule. The common currencies of the African franc zone reflect still strong political, as well as economic, linkage the former colonial power. The use of the U.S. dollar as the circulating medium in Panama (and Liberia) also reflects present or past political relationships. Moreover, the political theory of currency areas is not merely statement of static facts; it has predictive power. The common currency that Rome imposed throughout its empire did not survive the decline and fall of that empire. Similarly, the states that emerged from the breakups of the Austro-Hungarian and Ottoman empires after World War I rapidly moved separate currencies. When the Soviet Union collapsed at the end of 1991, some misguidedly thought that ruble zone could and should be preserved; but reality prevailed, and the 15 sovereign republics of the former Soviet Union all now have independent national currencies. Conversely, when the Founding Fathers sought construct a more perfect in the U.S. Constitution of 1787, the power to coin money and regulate the value thereof was transferred from the states the new federal government. The objective was not only improve the monetary basis for commerce and finance within and between the states, but also thereby strengthen their political union. In Europe today, the drive construct European Monetary Union (EMU) has been justified primarily on the prospective economic benefits of common currency. However, such proposal would have been literally unthinkable, whatever its possible economic benefits, with the political divisions that characterized Europe until relatively recent years. And, still today, the strongest advocates of EMU tend be those who see monetary union not only as beneficial economic mechanism, but also as substantively and symbolically important for strengthening the political dimension of European union. Conversely, those who are skeptical about stronger political union in Europe also tend be skeptical about EMU. In view of the centrality of political considerations in determining monetary arrangements, it seems essential ask how these considerations affect the differences between currency areas and currency unions, most importantly in the effort transform European monetary arrangements from currency area into EMU. A currency area is an arrangement for group of countries peg exchange rates among distinct national currencies. In some cases, exchange rates may be rigidly pegged, but more usually they are allowed fluctuate within narrow bands. Members retain their own central banks, although with serious constraints on the independence of national monetary policies. A currency union involves much stronger political and institutional commitment fix exchange rates absolutely through single money that functions as the monetary standard for group of countries. The supporting institutional structure also includes common monetary authority for all the countries of the union which determines monetary policy on union-wide basis. * Research Department, International Monetary Fund, Washington, DC 20431. The opinions expressed in this paper are solely those of the author and do not reflect the views of the International Monetary Fund.